A Comparison of Female Delinquents: The Impact of Child Maltreatment Histories on Risk and Need Characteristics among a Missouri Sample - Anne Dannerbeck-Janku; Clark Peters; Jacob Perkins (Laws, 2014)
While boys who offend have been a dominant majority and primary concern of the juvenile court since its earliest days, the population of delinquent girls has increased in recent years at a far higher rate in the U.S. The special challenges presented by females, however, continue to be generally overlooked by the justice system. Moreover, while a few specialized programs now serve these girls, the field tends to view young female offenders as a homogeneous group; what distinguishes particular female subpopulations and the characteristics associated with different criminal trajectories have gone largely unexplored. Employing data from the state of Missouri, this study examines girls who offend, identifying models that predict subsequent violent behavior that include indicators such as parental substance abuse and incarceration, and offender substance abuse, mental health, and school behavior. Special attention is given to the effects of child maltreatment, which we find significantly, but weakly correlated with violent behavior. The authors conclude by considering the possibility that maltreatment may be correlated with other criminogenic factors, and by discussing the implications of findings for future research and practice, especially services that take into account the trauma experienced by young women who come to the attention of state authorities.